Implementation of Constitutional Court Decision No. 46/PUU-VIII/2010 in the Examination of the Eligibility of Marriage Guardians for Children Born Out of Wedlock - Hardiyanto Putra Limonu; Nasrullah Nasrullah (Fox Justi : Jurnal Ilmu Hukum, 2026)
This research is motivated by the legal changes following the Constitutional Court Decision No. 46/PUU-VIII/2010, which opened the opportunity for recognizing civil relations between illegitimate children and their biological fathers. However, its implementation in the practice of examining the suitability of marriage guardians at the KUA (Religious Affairs Office) still faces several obstacles. The purpose of this research is to analyze how the decision is implemented at the KUA of Gorontalo City and to identify the obstacles that arise in administrative practice. The research uses an empirical legal approach through interviews with the head of the KUA and analysis of marriage examination documents, and is supplemented by a normative study of the Compilation of Islamic Law and the Constitutional Court Decision. The research findings indicate that the Office of Religious Affairs (KUA) still tends to rely on administrative documents as the basis for determining guardianship, and when evidence is deemed inadequate, appointing a guardian by a judge is the safest option. The Constitutional Court's ruling has not been fully implemented due to the lack of technical guidelines, limited staff capacity, and the influence of social factors and stigma. These findings underscore the need for harmonization of norms, clear technical guidelines, and strengthening institutional capacity to ensure more effective implementation of the rights of illegitimate children